Discourse Analysis: A Literature Study - Putri, Dinda Rahmadhani (Majapahit Journal of English Studies, 2025)
Discourse Analysis (DA) is a multidisciplinary approach to studying language use in social contexts. This article provides a comprehensive literature review of discourse analysis, focusing on its theoretical frameworks, methodologies, and applications in various fields. By examining recent studies (2020–2024), this paper highlights the evolving trends in discourse analysis, including its role in understanding power dynamics, identity construction, and digital communication. The findings underscore the importance of discourse analysis in uncovering hidden meanings and social structures embedded in language. This study concludes with recommendations for future research directions in discourse analysis.